Results of research of hypoxia problems by Ukrainian scientists in Elbrus region - Білошицький, П.В.; Ключко, О.М.; Онопчук, Ю.І. (Proceedings of National Aviation University (archive), 2022)
Results of some directions of many year studying of hypoxia problems is given. Investigations were carried at Elbrus medical and biological station and they are actual for aviation physiology and medicine. Results were obtained during field researches, using mathematical simulation. New methods of medical treatment developed on their base are described.